Digital Marketing in Cultural Institutions - Example of Cultural Institutions of the City of Zadar - Aleksandra Krajnović; Antonija Perković; Mladen Rajko (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Virtual Conference, 10-12 September 2020, 2020)
Marketing in public cultural institutions can be defined as a tool for achieving an organizational and creative concept that seeks to build relationships with the audience. This paper will define how public cultural institutions manage their marketing departments, with particular emphasis on the importance of using digital marketing channels on the example of cultural institutions in the City of Zadar. The research is based on four cultural institutions of the City of Zadar. Those institutions were examined by the structured in-depth interview method to explore the reach of using digital marketing in cultural institutions (public cultural institutions) on the example of the listed public cultural institutions. The paper also explores which digital marketing channels are being used for the scope of promotion in the listed cultural institutions. Furthermore, the importance of using social networks, mobile, email, and content marketing as a channel to interact with consumers of cultural institutions will be studied. The analysis of the primary research results will prove that the regular use of digital marketing channels has led to an increase in the number of visitors to cultural institutions.
Keywords: L30; L86; M31; M37; Z11; Z18; 330; digital marketing; non-profit marketing; cultural marketing; digital marketing channels; social networks